Regimiento de Artillería Antiaérea N.º 71 (Campamento, Madrid, 1978). Clases de Extensión Cultural - Juan Iglesias Alonso (Cabás)
Regimiento de Artillería Antiaérea N.º 71 (Campamento, Madrid, 1978). Clases de Extensión Cultural